An Analysis of Orthopedic Surgical Procedures Performed During U.S. Combat Operations from 2002 to 2016. Issue 11 (24th April 2019) - Stern, Caryn A; Stockinger, Zsolt T; Todd, William E; Gurney, Jennifer M
Abstract: Introduction: Orthopedic surgery constitutes 27% of procedures performed for combat injuries. General surgeons may deploy far forward without orthopedic surgeon support. This study examines the type and volume of orthopedic procedures during 15 years of combat operations in Iraq and Afghanistan. Materials and Methods: Retrospective analysis of the US Department of Defense Trauma Registry (DoDTR) was performed for all Role 2 and Role 3 facilities, from January 2002 to May 2016. The 342 ICD-9-CM orthopedic surgical procedure codes identified were stratified into fifteen categories, with upper and lower extremity subgroups. Data analysis used Stata Version 14 (College Station, TX). Results: A total of 51, 159 orthopedic procedures were identified. Most (43, 611, 85.2%) were reported at Role 3 s. More procedures were reported on lower extremities (21, 688, 57.9%). Orthopedic caseload was extremely variable throughout the 15-year study period. Conclusions: Orthopedic surgical procedures are common on the battlefield. Current dispersed military operations can occur without orthopedic surgeon support; general surgeons therefore become responsible for initial management of all injuries. Debridement of open fracture, fasciotomy, amputation and external fixation account for 2/3 of combat orthopedic volume; these procedures are no longer a significant part of general surgery training, and uncommonly performed by general/trauma surgeons at US hospitals. Given their frequency in war, expertise in orthopedic procedures by military general surgeons is imperative.